(untitled) (Research, Society and Development, 2021)
Hemophilia is a congenital and genetic hemorrhagic disease that is characterized by a deficiency of a plasma protein responsible for clotting, and affects more males due to an alteration in the X chromosome. Data were analyzed at the blood center of a region in northeastern Brazil. The objective of this study was to evaluate the epidemiological profile and treatment of coagulopathies in patients treated at the Blood Center during the years 2018 and 2019. In total, 242 patient records were analyzed, and tabulated in absolute frequency using epidemiological variables, type of hemophilia, and use of coagulation factors. The results showed that of the 242 patients with coagulopathies, 154 (63.6%) were male and 87 (36.4%), of these, 113 (47%) had hemophilia A, with a higher prevalence between 16 and 30 (43 %) years old. Hemophilia B 18 (8%) patients, aged between 36 and 50 (33%) years. Regarding the location, the urban region had the highest prevalence for patients with hemophilia type A. Of the 141 patients who received coagulation factor, 76 used recombinant Factor VIII, 66 used Urgent Home Dose (DDU) . The number of International Units (UI) dispensed with the highest proportion occurred in August 2018 and June 2019. It is concluded that the need to implement monitoring of patients who make use of coagulation factors, as well as the implementation of investments the federal government in order for the treatment to be continued.